PERANAN INTERNATIONAL ATOMIC ENERGY AGENCY UNTUK MENGAWASI PROGRAM NUKLIR IRAN DALAM KAITANNYA DENGAN IMPLEMENTASI JOINT PLAN OF ACTION 2013 - Ekpi Yoksara Simbolon; Sutiarnoto Sutiarnoto; Jelly Leviza (Journal of USU International Law, 2014)
ABSTRACT International Atomic Energy Agency has the main role in the nuclear field. It is the Agency’s programmes for promoting peaceful uses of nuclear technology, and also ensuring that State’s nuclear activities is not used to such any military purpose. It applies safeguard to deliver effective nuclear verification. The method used in this thesis is normative legal research by analyzing articles of International Treaties such as Statute, Charter, Convention and Agreement. The results showed that IAEA has the authority to implement monitoring and verification in relation to the nuclear-related measures set out in the Joint Plan of Action 2013. Monitoring and verification are to confirm that Iran has undertaken the “voluntary measures” during the first six months. IAEA has started to undertake monitoring and verification in relation to the measures set out in Joint Plan of Action. Keywords : IAEA, Iran’s Nuclear Programme, Joint Plan of Action 2013